Pengaruh Kepemimpinan Lembaga Pendidikan Tinggi Dalam Meningkatkan Mutu Pendidikan - Julianingsih P, L Eka M (STAHN Mpu Kuturan Singaraja, 2023)
The increasingly advanced challenges of globalization have an impact on almost all levels of human life, and it is possible that this will quickly hit the world of education, especially the provision of higher education in Indonesia. Globalization in a higher education institution will very rapidly influence a process of forming a new climate for learning and research carried out by a global network which will provide knowledge and information from various universities in the world as a whole. So universities are no longer considered to have a monopoly on knowledge, but in this era universities have to compete with other service providers therefore the quality of higher education institutions must continue to be improved. This research focuses on seeing how the influence of a leader in a higher education institution can improve the quality of education in the institution, where in this research the researcher uses qualitative descriptive methods to solve existing problems.